Selective Separation of Methane from Carbon Dioxide through sII Hydrates Formation in a Semibatch Process - Partoon, B. (American Chemical Society, 2019)
One of the challenges for production of natural gas from very sour gas reservoirs with CO2 content up to 80 is the high cost of purification process. The hydrate-based gas separation (HBGS) process is gaining interest globally as a greener solution for separation of CO2 from gaseous streams including sour hydrocarbon mixtures. However, separation of large amounts of CO2 through gas hydrate formation typically leads to considerable loss of hydrocarbons. In this work, selective capturing of CH4 from high CO2 gas mixtures is investigated. Two water-soluble thermodynamic promoters, tetrahydrofuran (THF) and acetone, are used for this purpose. The results indicate that inclusion of these promoters dramatically increased CH4 uptake by sII hydrate formation. However, only THF exhibited a favorable selectivity of CH4. Moreover, this effect is pressure dependent, and the optimum pressure is around 4.5 MPa. Copyright Â© 2019 American Chemical Society.